2017
DOI: 10.21608/jssae.2017.38191
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mineral Fertilization Rate and Foliar Application of Yeast and Ascorbic Acid on Yield, Vegetative Growth and Fruits Quality of Eggplant.

Abstract: The experiments were carried in clay soil at the Experimental Farm of Faculty of Agricultural, El-Mansoura University, Egypt, to investigate the effect of foliar application with yeast and ascorbic acid on plant growth, yield and quality of eggplant (Solanum melongena L.) under different levels of NPK fertilization. Vegetative growth measurements (plant height, No. of leaves/plant, No. of branches/plant, fresh and dry weight), yield (fruits length, fruit diameter, No. of fruits and total yield), N, P, K and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Also, the increases in dry weight of shoots/ plant were about 28.56 and 32.71 g over the control in the 1 st and 2 nd seasons, respectively. Foliar spray with yeast extracts increased growth parameters of eggplant (El-Tohamy et al ,2008 ;El-Nemr et al, 2015 ;El-Sayed et al, 2015 ;Fouda and Abd-Elhamied, 2017;Ahmed et al 2021).…”
Section: Effect Of Spraying With Some Safety Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the increases in dry weight of shoots/ plant were about 28.56 and 32.71 g over the control in the 1 st and 2 nd seasons, respectively. Foliar spray with yeast extracts increased growth parameters of eggplant (El-Tohamy et al ,2008 ;El-Nemr et al, 2015 ;El-Sayed et al, 2015 ;Fouda and Abd-Elhamied, 2017;Ahmed et al 2021).…”
Section: Effect Of Spraying With Some Safety Materialsmentioning
confidence: 99%
“…Foliar spray with yeast extracts increased growth parameters, yield and fruit quality of eggplant (El-Tohamy et al ;El-Nemr et al, 2015El-Sayed et al, 2015 ;Fouda and Abd-Elhamied, 2017;Ahmed et al , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, El-Sherbeny et al (2007), Saleh et al (2010), Abbas (2013), Fouda et al (2017) and Alsaady et al (2020), who sprayed plants with yeast extracts showed that yeast extract significantly increased the pigments content of plants.…”
Section: Leaves Pigments Contentmentioning
confidence: 99%
“…These results may be due to yeast extract was stimulatory effects on protein, cell division, nucleic acid synthesis, enlargement and chlorophyll formation also, participates in a useful role during stress according to its cytokinins content.These results are in agreement with those obtained by Barnett et al (1990), El-Tohamy et al(2008 on eggplant , Fathy et al (2000) on tomatoes, Taha and Omar (2010) and Ahmed et al(2011) on potato plants. Fouda and Abd-Elhamied et al(2017).…”
Section: -Effect Of Plant Stimulants Treatmentsmentioning
confidence: 99%
“…Its stimulatory effects on protein, cell division, DNA synthesis, hypertrophy and chlorophyll formation have also been emphasized, and it also participates in a beneficial role during stress according to its cytokinin content (Barnett et al, 1990). El-Tohamy et al,(2008) on eggplant, Fathy et al(2000) on tomatoes, Taha and Omar (2010), Ahmed et al (2011) on potato andFouda andAbd-Elhamied et al(2017) all of them found that using active yeast extract improved the growth and productivity of vegetable crops.…”
Section: Introductionmentioning
confidence: 99%